2017
DOI: 10.1038/s41598-017-16660-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen motion in rutile TiO2

Abstract: Uniaxial-stress experiments have been performed for the 3287- and 2445-cm−1 local vibrational modes assigned to the positive charge state of interstitial hydrogen and deuterium , respectively, occurring in mono-crystalline rutile TiO2. The onset of the defect alignment under the stress applied perpendicular to the [001] axis is detected at 165 K (185 K), which corresponds to the activation energy of 0.53 eV (0.58 eV) for interstitial hydrogen (deuterium). Based on these findings the diffusion constants of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 52 publications
5
21
0
Order By: Relevance
“…This finding demonstrates the strong anisotropy in the migration of hydrogen and agrees with the existing experimental diffusion data [15,38]. More specifically, the energy barrier E barr for the proton-transfer T3 path is extremely high (2.30 eV), very likely owing to the rather large hopping length for hydrogen (equal to 2.89 Å).…”
Section: Atomistic Mechanisms Of Hydrogen Migrationsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding demonstrates the strong anisotropy in the migration of hydrogen and agrees with the existing experimental diffusion data [15,38]. More specifically, the energy barrier E barr for the proton-transfer T3 path is extremely high (2.30 eV), very likely owing to the rather large hopping length for hydrogen (equal to 2.89 Å).…”
Section: Atomistic Mechanisms Of Hydrogen Migrationsupporting
confidence: 89%
“…The present results for E a slightly underestimate the experimentally derived activation energies of hydrogen diffusion parallel to the c axis: an activation energy of 0.59 eV was obtained by Johnson et al [15] from high-temperature diffusion data (the temperature range was from 350°C-700 °C). A recent work has extended diffusion measurements to lower temperatures (from 157 K to 197 K) by studying stressed-induced dichroism of the local vibrational modes due to hydrogen and deuterium [38]. These authors reported an overall activation energy equal to 0.54 eV by combining high-temperature and low-temperature data.…”
Section: Diffusion Rate and Coefficient Along The C Axismentioning
confidence: 99%
“…Relatively simple theoretical model with single V O and single H* is presented here. Previous reports show that applied strain effects diffusion pathways and overall distribution of H*s on rutile TiO 2 53,56 . Strain also affects formation, diffusion and energy of V O s, as discussed throughout the text.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, H is also likely to form complexes with various other defects [232]. Notably, H has a large diffusion coefficient in r-TiO 2 [241], and it has been shown that H can in-diffuse into r-TiO 2 during heat-treatments even if H is only present as a residual impurity in the annealing atmosphere [125].…”
Section: Defects In Rutile Titanium Dioxidementioning
confidence: 99%